2016
DOI: 10.1074/mcp.m116.058081
|View full text |Cite
|
Sign up to set email alerts
|

The Salivary Protein Repertoire of the Polyphagous Spider Mite Tetranychus urticae: A Quest for Effectors

Abstract: The two-spotted spider mite Tetranychus urticae is an extremely polyphagous crop pest. Alongside an unparalleled detoxification potential for plant secondary metabolites, it has recently been shown that spider mites can attenuate or even suppress plant defenses. Salivary constituents, notably effectors, have been proposed to play an important role in manipulating plant defenses and might determine the outcome of plant-mite interactions.Here, the proteomic composition of saliva from T. urticae lines adapted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 131 publications
4
128
0
Order By: Relevance
“…Quantitative differences in the expression levels of effector‐encoding genes have also been observed between virulent and avirulent isolates of filamentous phytopathogens when infecting plants and, hence, are thought to determine their degree of virulence (Cooke et al ., ; Hacquard et al ., ). Consistently, when feeding from tomato, the transcript abundances of these ( Te28 , Tu28 , Te84 and Tu84 ) and (putative) other (Jonckheere et al ., ) spider mite effector‐encoding genes probably affect the magnitude of key defenses and concomitantly the performance of the mites. Given that the magnitude of JA and SA defenses reported here (Figs 1–5) correlates well with the transcript levels of mite effector‐encoding genes (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Quantitative differences in the expression levels of effector‐encoding genes have also been observed between virulent and avirulent isolates of filamentous phytopathogens when infecting plants and, hence, are thought to determine their degree of virulence (Cooke et al ., ; Hacquard et al ., ). Consistently, when feeding from tomato, the transcript abundances of these ( Te28 , Tu28 , Te84 and Tu84 ) and (putative) other (Jonckheere et al ., ) spider mite effector‐encoding genes probably affect the magnitude of key defenses and concomitantly the performance of the mites. Given that the magnitude of JA and SA defenses reported here (Figs 1–5) correlates well with the transcript levels of mite effector‐encoding genes (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Although previous proteome studies on spider mites identified about 90 and 177 putative SGPs from T. urticae and Tetranychus truncates (Jonckheere et al ., ; Zhu et al ., ), neither Tet1 nor Tet2 was listed among them. However, we observed that Tet1 is expressed predominantly in the anterior podocephalic salivary glands, possibly together with the silk glands, of T. urticae , implying that Tet1 is secreted outside of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of induced plant defenses was proposed to be the common and most efficient 183 mechanism of TSSM adaptation to new host plants (Jonckheere et al, 2016;Villarroel et al, 184 2016; Blaazer et al, 2018;Jonckheere et al, 2018). Indeed, interference with either JA-185 biosynthesis or its signalling appears to be an effective way to attenuate a whole range of 186…”
Section: Arabidopsis-adapted Mites Do Not Suppress Arabidopsis Defensmentioning
confidence: 99%
“…Arabidopsis-adapted mites are responsive to Arabidopsis xenobiotics 213 Metabolic resistance is another mechanism of herbivore adaptation to xenobiotic challenges 214 previously implicated in the evolution of TSSM resistance to pesticides (Van Leeuwen and 215 Dermauw, 2016) On the ancestral bean plants, all marker transcripts were at similar low levels in both bean-and 230…”
Section: Arabidopsis-adapted Mites Do Not Suppress Arabidopsis Defensmentioning
confidence: 99%